Timing of Delivery for Twins With Growth Discordance and Growth Restriction: An Individual Participant Data Meta-analysis. Issue 6 (2nd June 2022) - Koch, Ashlee K.; Burger, Renée J.; Schuit, Ewoud; Mateus, Julio Fernando; Goya, Maria; Carreras, Elena; Biancolin, Sckarlet E.; Barzilay, Eran; Soliman, Nancy; Cooper, Stephanie; Metcalfe, Amy; Lodha, Abhay; et al.
Abstract : An individual patient meta-analysis does not support that the optimal timing of delivery for twin pregnancies should be changed by the presence of growth disorders alone. Abstract : OBJECTIVE: First, to evaluate the risks of stillbirth and neonatal death by gestational age in twin pregnancies with different levels of growth discordance and in relation to small for gestational age (SGA), and on this basis to establish optimal gestational ages for delivery. Second, to compare these optimal gestational ages with previously established optimal delivery timing for twin pregnancies not complicated by fetal growth restriction, which, in a previous individual patient meta-analysis, was calculated at 37 0/7 weeks of gestation for dichorionic pregnancies and 36 0/7 weeks for monochorionic pregnancies. DATA SOURCES: A search of MEDLINE, EMBASE, ClinicalTrials.gov, and Ovid between 2015 and 2018 was performed of cohort studies reporting risks of stillbirth and neonatal death in twin pregnancies from 32 to 41 weeks of gestation. Studies from a previous meta-analysis using a similar search strategy (from inception to 2015) were combined. Women with monoamniotic twin pregnancies were excluded. METHODS OF STUDY SELECTION: Overall, of 57 eligible studies, 20 cohort studies that contributed original data reporting on 7, 474 dichorionic and 2, 281 monochorionic twin pairs. TABULATION, INTEGRATION, AND RESULTS: We performed an individual participant data meta-analysis to calculate the risk of perinatal death (risk difference between prospective stillbirth and neonatal death) per gestational week. Analyses were stratified by chorionicity, levels of growth discordance, and presence of SGA in one or both twins. For both dichorionic and monochorionic twins, the absolute risks of stillbirth and neonatal death were higher when one or both twins were SGA and increased with greater levels of growth discordance. Regardless of level of growth discordance and birth weight, perinatal risk balanced between 36 0/7–6/7 and 37 0/7–6/7 weeks of gestation in both dichorionic and monochorionic twin pregnancies, with likely higher risk of stillbirth than neonatal death from 37 0/7–6/7 weeks onward. CONCLUSION: Growth discordance or SGA is associated with higher absolute risks of stillbirth and neonatal death. However, balancing these two risks, we did not find evidence that the optimal timing of delivery is changed by the presence of growth disorders alone. SYSTEMATIC REVIEW REGISTRATION: PROSPERO, CRD42018090866.